Effects of Opioid Antagonism on Cerebrospinal Fluid Melanocortin Peptides and Cortisol Levels in Humans - Gordon, Rebecca J. (J Endocr Soc, 2017)
CONTEXT: Hypothalamic proopiomelanocortin (POMC) is processed to α-melanocyte-stimulating hormone, which interacts with the melanocortin antagonist agouti-related protein (AgRP), to regulate energy balance. The POMC-derived opioid peptide β-endorphin (β-EP) also affects feeding behavior via interactions with brain µ-opioid receptors (MORs), including autoinhibitory interactions with MOR expressed by POMC neurons. The opioid antagonist naltrexone (NTX) stimulates POMC neurons in rodents and decreases food intake. OBJECTIVE AND DESIGN: The effect of NTX on brain POMC in humans was assessed by measuring POMC peptide concentrations in lumbar cerebrospinal fluid (CSF). AgRP and cortisol levels were also measured because both are inhibited by opioids. In a double-blinded crossover study, 14 healthy subjects were given NTX (50 mg daily) or placebo for either 2 or 7 days. RESULTS: CSF β-EP levels increased after 2 and 7 days of NTX treatment; CSF POMC levels did not change, but the β-EP-to-POMC ratio increased. CSF AgRP levels did not change, but plasma AgRP levels tended to increase after NTX (P = 0.06). Cortisol increased in plasma and CSF after NTX treatment; these changes correlated positively with changes in AgRP levels. CONCLUSION: Opioid antagonism stimulates POMC peptide release into CSF in humans. The increase in the CSF β-EP-to-POMC ratio could indicate selective release of processed peptides or an effect on POMC processing. Furthermore, AgRP and cortisol stimulation by NTX may mitigate POMC-induced decrease in food intake. It remains to be determined if biomarkers in CSF and plasma could be used to predict responses to pharmacotherapy targeting the melanocortin system.